REPRESENTASI LAKI-LAKI BUDAYA SUNDA DALAM FILM ROCKER BALIK KAMPUNG KARYA ULI RAHMAN (KAJIAN SEMIOTIKA) - Hera Juliana; Fajar Sukma Nur Alam (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
The diversity of cultures, especially regional languages, in the course of time can influence the modernization of cultural traditions. One such event is depicted in the story or synopsis of the film Rocker Balik Kampung by Uli Rahman, which is used as a case study to observe how visual media plays a role in shaping the perception and cultural identity of society. As an audio-visual medium, film has the ability to capture social and cultural realities and convey messages through visual representation. Based on Charles Sanders Peirce's semiotic theory, this research analyzes the signs in the film that form cultural narratives and their interpretations by the audience. The purpose of this research is to analyze the representation of Sundanese male culture and examine the meanings and values in Uli Rahman's film Rocker Balik Kampung. This research uses descriptive analysis methods and data collection techniques through observation and note-taking. The instrument used is data cards. The research results on the representation of Sundanese male culture include 28 scenes categorized into signs, objects, and interpretants; 20 scenes are categorized into meanings and values according to Stuart Hall's representation theory, depicting the main character, Juhana, bringing modernization to the traditional village of Sinar Asih, which is deeply rooted in ancestral traditions. Using Charles Sanders Peirce's semiotic theory and Stuart Hall's perspectives, this film explores the representation of males in Sundanese culture and the dynamics between tradition and modern change. This representation reflects how traditional identities and values can adapt to modern elements within social and cultural contexts.